GCS AS PREDICTOR LENGTH OF STAY THE MILD HEAD INJURY PATIENTS IN PIRNGADI GENERAL HOSPITAL MEDAN - Normi Parida Sipayung; Henny Syapitri (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2015)
Introduction. Early management of head injury patient in Emergency Department will affect the outcome and Length of Stay mild head injury patient in the hospital. The research aimed to analyze GCS as predictor factors associated Length of Stay patient in the hospital. Methods. This study was correlational analytic approach with cross sectional. Technique sampling in this study used purposive sampling. The number of samples used 41 patient were taken from the primary data which doing the observations on the mild head injury patients who come to emergency department from April until June 2014 at Pirngadi General Hospital Medan. Data was collected by observation and questionnaire. Result. The results of the analysis used Spearman test showed that there was correlation between GCS with Length of Stay of mild head injury patients p 0.00, r -0,637. Discussion. Higher value of GCS So length of stay a mild head injury patients in Pirngadi General Hospital Medan also shorter .Keywords: Mild head injury, outcome head injury, predictor Length of Stay, Emergency Department